Inhospital Exercise Training in Children With Cancer: Does It Work for All? - Morales, Javier S.; Padilla, Julio R.; Valenzuela, Pedro L.; Santana-Sosa, Elena; Rincón-Castanedo, Cecilia; Santos-Lozano, Alejandro; Herrera-Olivares, Alba M.; Madero, Luis; San Juan, Alejandro F.; Fiuza-Luces, Carmen; Lucia, Alejandro (Frontiers in Pediatrics, 2018)
Purpose: Physical exercise training might counteract the weakening effects of both pediatric cancer and anti-cancer treatment. We aimed to analyze the prevalence of “responders” and “non-responders” to inhospital exercise training in children with cancer and to identify the factors that could influence responsiveness, which might help personalize exercise interventions for this patient population. Methods: We performed an ancillary analysis of the randomized controlled trial “Physical activity in Pediatric Cancer” (NCT01645436), in which 49 children with solid tumors were allocated to an inhospital exercise intervention or control group. The present study focused on the children in the former group (n = 24, 10 ± 4 years), who performed 3 weekly training sessions (aerobic + strength exercises). The intervention lasted 19 ± 8 weeks (i.e., from the start to the end of neoadjuvant chemotherapy treatment). A responder-vs-non-responder analysis was performed for physical capacity-related endpoints (five-repetition maximum strength, functional mobility tests, and cardiorespiratory fitness [CRF]). Only those participants showing improvements in a given test of a magnitude greater than both the random error and the threshold for clinically meaningful changes were considered responders. Results: Most participants improved their performance in the strength tests, with 80, 88, and 93% of total showing a positive response for seated bench press, lateral row, and leg press, respectively (p < 0.001). No significant improvements were observed for the functional mobility tests or CRF (p > 0.05, rate of responsiveness ≤ 50%). No differences between responders and non-responders were observed for sex, age, type of cancer, or treatment (i.e., including or not anthracyclines/radiotherapy). However, significant differences (p < 0.05) were observed between responders and non-responders for baseline performance in all the tests, and a significant (p < 0.05) inverse relationship was found between baseline performance and relative improvement for most endpoints. Conclusions: Although most children improved their muscle strength after the exercise intervention, a considerable individual variability was observed for the training responsiveness of functional mobility and CRF. A lower baseline performance was associated with a higher responsiveness for all the study endpoints, with the fittest children at the start of treatment showing the lowest responses. Efforts to individualize exercise prescription are needed to maximize responsiveness in pediatric cancer patients.